Impact of Control Interventions on Malaria Incidence in the General Population of Mali - Mady Cissoko; Issaka Sagara; Abdoulaye Guindo; Mahamane Maiga; Pascal Dembélé; Cedric S. Bationo; Sokhna Dieng; Issa Diarra; Abdoulaye Katilé; Diahara Traoré; Nadine Dessay; Jean Gaudart (Journal of Epidemiology and Global Health)
Abstract Background The increase in malaria incidence and the reduction of funding for malaria control have highlighted the need to step up efforts in the fight against malaria in Mali. To further refine the malaria control strategy implemented in the country, this study aimed to evaluate the impact of control interventions at the health district level on malaria incidence in the general population. Method Malaria, rainfall, and intervention data were collected for the 75 health districts of Mali for the period from April 2017 to March 2022. The impact of the different control interventions on malaria incidence in the general population was assessed at the health district level with a Generalized Additive Mixed Model considering rainfall. Results Although coverage rates varied widely between health districts, most interventions showed an improvement in coverage over the study period. Two interventions had a small impact on incidence: long-lasting insecticidal net mass distribution (LLIN), with a reduction rate of 2.2 ‰ for an adjusted coverage rate from 30.0 to 79.0% (odds ratio (OR): 0.998; 95% confidence interval (CI) 0.997–0.999), and seasonal malaria chemoprevention (SMC), with a reduction rate of 1.9 ‰ for an adjusted coverage rate from 30.0 to 80.0% (OR: 0.9979; 95% CI 0.996–0.998). Conclusion The analysis found a small impact of LLIN and SMC on malaria incidence at the district level. Malaria control should be reinforced by improving coverage and utilization rates in the general population and in the most vulnerable groups and by deploying larger numbers of community health workers where needed.